Feminist and Philosophical Dimensions of Motherhood in Simin Behbahani’s Poetry - Shirazi, Ali Ahmad; Haider, Muhammad Irfan (Makhz (Research Journal), 2025)
The present study offers a critical and intellectual analysis of the portrayal of women's social roles—particularly the role of the mother—in the poetry of the renowned Persian poet Simin Behbahani. Her poetry transcends mere emotional or aesthetic expression and instead presents the woman, especially the mother, as a conscious, autonomous, and resistant figure. The research explores the maternal role through selected poetic excerpts, analyzing its emotional, symbolic, and ideological dimensions. Behbahani does not confine motherhood to affection or nurturing alone; rather, she elevates the figure of the mother as a voice of social injustice, political unrest, national grief, and human empathy. This study adopts an analytical methodology rooted in feminist literary criticism, aiming to interpret the poetic texts within their socio-political and intellectual contexts. The findings highlight that in Behbahani’s poetic universe, the mother is not merely a domestic being but a symbol of resistance and active femininity, embodying sacrifice, patience, and awareness. Her poetry blends the inner anguish of women with collective consciousness, crafting a powerful, dignified, and empowered image of womanhood in the reader’s mind.